PROFESIONALISME PEGAWAI NEGERI SIPIL DALAM PELAYANAN PUBLIK PADA KANTOR TERPADU SATU PINTU KABUPATEN SIDENRENG RAPPANG - Monalisa Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This research was conducted in 2015 with the objective to know the professionalism of Civil Servants in One Stop Service Office of Sidenreng Rappang Regency and determinant factors related to Civil Servant professionalism in providing license issuing service at One Stop Service Office of Sidenreng Rappang Regency. Research location at One Stop Service Office of Sidenreng Rappang District. Data collection techniques used: a) observation, b) questionnaires, c) interviews, and d) documentation. Data analysis techniques use quantitative descriptive. Based on the results of the research described in Chapter 4 above, the authors can be concluded that the professionalism of civil servants in public service in integrated service office one door kab. Sidrap is already good, it can be seen from the results of research through research indicators, such as; 1) Honesty of civil servants, 2) Work ethic owned by civil servants, 3) Creativity owned by civil servants, 4) Obstacles in running the rules, 5) Timeliness in the execution of duties and functions, 6) Simplicity, 7) Economical, 8) Fast, 9) Means and prasaranan, 10) Motivation work, 11) Leadership.